Alternatif Perencanaan Bangunan Pengaman Pantai Tipe Groin di Desa Hatu Kabupaten Maluku Tengah - Lusiasmianti; Benyamin Tanan; Herman Welem Tanje (Paulus Civil Engineering Journal, 2022)
This study aims to prevent abrasion and restrain sediment transport along the coast with a groyne type in Hatu village. This research is used as consideration for the construction of other coastal protection constructions around the sea. The high waves on the Hatu beach result in the erosion of the coastline due to the erosion that occurs, thus endangering the safety of the lives of local residents. Wind data analysis uses WindRose software to understand the dominant wind direction. According to the forecast, the majority of the wind waves used the fetch length according to the Shore Protection Manual (SPM) 1984. The planning wave was determined using the Fisher Tipped Type I method using a two-hundred year return period. Determination of sedimentation along the coast and planning of buildings in the book Planning of Coastal Buildings by Bambang Triatmodjo and Wilson's Method by Kiyoshi Horikawa. Obtained from the study, the majority of the wind direction is from the southeast. The design wave height in the 50-year return period is 2,605 m. The base of the groyne is planned to start from the elevation ( + 0.00 HWL) from the sea line using a depth of -2.894 m. The planned groyne type is type I which has two layers.